Host-parasite interaction: Changes in human placental gene expression induced by Trypanosoma cruzi - Castillo, Christian (2018)
Background: Chagas disease is caused by Trypanosoma cruzi, a parasite endemic to Latin America. Most infections occur in children by vector or congenital transmission. Trypanosoma cruzi establishes a complexity of specific molecular parasite-host cell interactions to invade the host. However, most studies have been mainly focused on the interaction between the parasite and different cell types, but not on the infection and invasion on a tissue level. During congenital transmission, T. cruzi must cross the placental barrier, composed of epithelial and connective tissues, in order to infect the developing fetus. Here we aimed to study the global changes of transcriptome in the placental tissue after a T. cruzi challenge. Results: Strong changes in gene expression profiling were found in the different experimental conditions, involving the reprogramming of gene expression in genes involved in the innate immune response. Conclusions: Trypanosoma cruzi induces strong changes in genes involved in a wide range of pathways, especially those involved in immune response against infections.